United Kingdom : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper estimates the extent of spare capacity in the U.K. economy using a range of methodologies pointing to an output gap and the behavior of inflation during large output gaps. The usefulness of fiscal rules in supporting fiscal consolidation is generally positive, and a more permanent rules-based fiscal framework is required. The banking system has recovered fast; however, the sustainability of the sector's recovery is still uncertain, and risks remain. An update on reforms to the financial sector's regulatory and supervisory framework is also provided.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet